O Conselho Municipal de Educação: desafios e possibilidades na gestão das políticas educacionais - LEAL, Patrícia Alessandra Gomes (2024)
This study focuses on the Municipal Education Councils (CMEs) of São Luís andPaço do Lumiar. Its main objective is to analyze the performance of the MunicipalEducation Councils in the context of defining, monitoring, implementing, and evaluating the guidelines of municipal educational policies from 2018 to 2022. This is achieved through the laws of the Municipal Education Plans, Multi-Year Plans, Articulated Action Plans, Laws establishing the CMEs, complementary and regulatory laws, their Internal Regulations, direct observation, and qualitative interviews with an epistemological orientation based on historical-dialectical materialism. The study of the research data will be carried out using content analysis, as suggested by Bardin (1977), through the different phases: pre-analysis, material exploration, result processing through inference, and interpretation. The deepening of studies occurs through a literature review, starting with a state-of-the-art survey conducted on the CAPES platform, which included publications on CMEs from 2014 to 2020. The literature review also includes studies by authors such as Kosik (1976), Cury (2000), Santos (2001), Bordignon (2009), Oliveira (2009, 2014), Cardozo (2009), Farias (2012), Saviani (2008, 2013), Campos (2013), and Freitas (2018), focusing on changes in policies since the 1990s within the context of State Reform. Regarding democratic management: Challenges and Perspectives in Education, the concepts of autonomy and participation are considered. In the context of decentralization, our understanding is based on studies by Oliveira (2009), Dublante (2011), Libâneo (2018), Clemente (2018), Cardozo and Colares (2018), Santos, Cardozo, and Rodrigues (2024), among others. Santos (2001), Farias (2012), Bordignon (2009and 2020), and Cury (2000 and 2006), among others, expanded and strengthened the knowledge about the Education Councils, their roles, functions, nature, historical framework, and legal bases, considering their foundations in the principles of social control and democratic management. Regarding municipal education councils and education management and the challenges and possibilities in the management of educational policies, the studies carried out by Cardozo and Colares (2018), Bordignon (2020), Flach (2020), Santos, Cardozo and Rodrigues (2024 ), among others.Field research will be conducted through direct observation and interviews with council members of the Education Councilsthe municipalities of São Luís and Paço do Lumiar.. We conclude that the CMEs of São Luís and Paço do Lumiar constitute allies in the fight for the democratization of public educational policies, in the strengthening of proposals/projects that correspond to the aspirations and educational needs of the working class, as the majority in the composition of public schools respective municipalities.